Remarks on the theory of hearing-a traveling wave part two - Jan Myjkowski (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2022)
In the paper, attention was paid to the procedure of reception and transforming auditory information, which does not comply with Bekesy's traveling wave theory. This concerns the sound reception below the hearing threshold in some animals and birds. Discussed are some issues related to the traveling wave theory with an explanation of directional hearing. Indicated was a possibility of reception, especially, of high frequencies, directly on the receptor, without the basilar membrane, due to the conduction of sound waves through soft tissues and a bone.